Pengaruh Perlakuan Teknologi Amofer (Amoniasi Fermentasi) Pada Limbah Tongkol Jagung Sebagai Alternatif Pakan Berkualitas Ternak Ruminansia - Dewi Hastuti; Shofia Nur Awami; Baginda Iskandar M (Universitas Wahid Hasyim, 2011)
Forage quality and are available continuously throughout the year is one important factor in the development of animal husbandry. The potential is quite abundeant corn corp has not been optimally utilized as livestock feed. The weakness of corn cobs as feed is a high fiber content (35 – 45%) and low protein levels (1,8 – 3,5%). Amoniasi fermentation (Amofer) is one way of improving the quality of high-fiber feed ingredients are quite powerful. The purpose of this study was to assess the effect of curing time on the fermentation process using biostarter (Biofad) on a cob of corn that had previously been amoniasi with high temperature (70°C) on the proximate content. The results of proximate analysis of corn cobs with amofer treatment showed increased levels of crude protein and highest in long curing 2 weeks (34,20%), crude fat content (2,29%) higher than the fat content of coarse corn cobs controls (1,86%), crude fiber content of 25,43% on average much lower than control levels of crude fiber (34,78%), ash content increased significantly (3,11% - 4,15%) and the average levels BETN 36,45% lower than the control corn cob (57,50%). Old curing 2 weeks in the fermentation process gives the best result, because it has the highest protein content and low crude fiber and have long curing the fastest time. Key words : corn cob, amofer, curing